The problems and perspectives of the training of applied mathematicians - Ivanauskas, Feliksas; Pekarskas, Vidmantas (Lietuvos matematikos rinkinys, 2002)
The article gives a survey of the problems and perspectives of the training of applied mathematicians. The syllabus of applied mathematics is discussed too.